Assessing the conjugacy of the marine economy-ecology-society composite system: China’s Case - Zhang, Cai; Wang, Miao (Frontiers in Marine Science, 2022)
As of now, the development and utilization of marine resources have entered a new stage of “refinement, orderliness, and high quality”. It has become a top priority to coordinate the relationship among marine economy, ecology, and society. At the same time, the comprehensive evaluation of the conjugacy of the marine composite system has replaced the single evaluation that only relies on economic indicators to measure the operation effect of the marine system. The operational effect of the marine system needs to be comprehensively measured from three aspects: the profitability of the marine economic subsystem, the sustainability of the marine ecological subsystem and the effectiveness of the marine social subsystem. The combination of composite ecosystem theory and conjugate ecosystem theory was applied to the marine economic-ecological-social composite system, the concept of “conjugate degree of marine composite system” was proposed, the conjugate mechanism of marine composite system subsystem was discussed, the conjugate degree measurement model and prediction model of marine composite system were constructed, the conjugate degree measurement index system of marine composite system was constructed, and the cases of China’s coastal areas were empirically analyzed. The empirical results show that 1) the conjugation degree of the marine composite system in Shandong Province is in a steady growth and “moderate conjugation” state. 2)The conjugation degree of marine composite systems in China’s coastal areas is mostly in the state of “low conjugation”. 3)The balance development of the three subsystems of marine economy, ecology and society is the basic premise of the high conjugate degree of the marine composite system.4) It is unscientific and unreasonable to measure the development of the marine system by the gross marine product. Finally, the policy recommendations for the conjugate development of the marine composite system were proposed. The multi-objective comprehensive evaluation of ocean system operation was explored to provide decision support and policy basis for promoting the balanced, sustainable and high-quality development of ocean system.